Efficacy of prolonged elemental diet therapy after pancreaticoduodenectomy for pancreatic ductal adenocarcinoma: A pilot prospective randomized trial (UMIN000004108). (December 2019) - Mori, Ryutaro; Matsuyama, Ryusei; Taniguchi, Koichi; Goto, Koki; Miyake, Kentaro; Hiratani, Seigo; Homma, Yuki; Ohta, Yohei; Kumamoto, Takafumi; Morioka, Daisuke; Endo, Itaru
Summary: Backgrounds and aims: This randomized clinical trial examined efficacy of prolonged elemental diet (ED) therapy after pancreatoduodenectomy (PD) for pancreatic ductal adenocarcinoma (PDAC), which often causes postoperative malnutrition leading to worsened short- and long-term outcomes. Methods: Thirty-nine patients with PDAC receiving PD was randomly assigned to prolonged ED group (PEDG) and control group (CG). Fat-free ED (Elental®, EA Pharma CO., Ltd., Tokyo, Japan) via tube jejunostomy was initiated on postoperative day 1 and increased to maintain with 600 kcal/day in addition to oral intake. ED was discontinued if sufficient oral intake was achieved in CG but continued during 3 postoperative months in PEDG. Primary outcome was complication necessitating readmission. Secondary outcomes were nutritional parameters, relative dose intensity (RDI) in cases of adjuvant chemotherapy, and survival outcomes. Results: Twenty patients were assigned to CG and 19 to PEDG. Cumulative post-discharge readmission rate was significantly lower in PEDG than in CG (PEDG vs CG; 12.6% vs 43.7% at 12-post-discharge-month; p = 0.018). Total calorie and ED-derived protein intakes were significantly larger in PEDG than in CG up to 3-postoperative-month but thereafter similar among groups. Lymphocyte counts were significantly increased and neutrophil-to-lymphocyte-ratio (NLR) was significantly reduced in PEDG than in CG at 2-, 3-, and 6-postoperative-month. However, other outcome measures did not differ among groups. Conclusion: This trial failed to show survival benefit of prolonged ED therapy but demonstrated its favorable effect on increased lymphocyte counts, reduced NLR, and prevention of complications necessitating readmission, those which may lead to survival benefit with some modifications.